PENGARUH MODEL PEMBELAJARAN DISKURSUS MULTI REPRESENTASI (DMR) TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI TEKNIK PEMESINAN SMKN 1 SUMATERA BARAT - Rianti, Dian Meisya (Departemen Matematika, 2024)
Mastery of mathematical concepts is an important goal in education because it can improve students' ability to understand the subject matter. Grade XI Mechanical Engineering at SMKN 1 West Sumatra still has a long way to go before students fully understand mathematical concepts. It is suggested that the Discourse Multi Representation (DMR) learning paradigm be used to address the problem. This study aims to investigate how grade 11 students enrolled in the Mechanical Engineering program at SMKN 1 West Sumatra fare in their attempt to use the DMR learning model and how the model affects their understanding. The research conducted was a quasi-experimental study. The participants in this study were grade XII students at SMKN 1 West Sumatra who majored in machining engineering. Quizzes and exams were the assessment tools. The results showed that the DMR learning model was significantly better based on the quiz development results. A P-value of 0.000, which is less than 0.05, was generated from the data analysis, specifically the Mann-Whitney test. This proves that H0, the null hypothesis, is not true. Thus, students' understanding of mathematical concepts improved with the DMR method when compared to the traditional learning methodology.Keywords– DMR Model, Understanding of Mathematical Concepts